THE ROLE OF LITERATURE IN THE FORMATION OF YOUTH CULTURE (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
the article describes the important role of literature of the young generation, education in the spirit of patriotism, high civic consciousness, devotion to ideals, and others. The article also presents the works of great poets and their invaluable heritage, which are imbued with the ideas of humanism and philanthropy.